2014
DOI: 10.4319/lo.2014.59.3.1095
|View full text |Cite
|
Sign up to set email alerts
|

On database biases and hypothesis testing with dilution experiments: Response to comment by Latasa

Abstract: Response

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The large variability observed at stations on the plateau was mainly due to the remarkably low values obtained at Station 21 (minimum rates across the study, μ 0 = 0.09, grazing = 0.18), where the dilution experiment rendered nonsignificant relationship between apparent growth and dilution factor ( R 2 = 0.02, Table ). Although the exact magnitude of these rates should be regarded with caution, we consider that the low rates obtained represent a valid experimental outcome that can contribute meaningfully to the broader interpretation of growth and grazing variability in this region (Landry, ; Latasa, ). Taken together, photo‐physiological measurements and growth rates estimated at stations on the plateau suggested a physiological improvement of phytoplankton relative to waters off the plateau.…”
Section: Discussionmentioning
confidence: 92%
“…The large variability observed at stations on the plateau was mainly due to the remarkably low values obtained at Station 21 (minimum rates across the study, μ 0 = 0.09, grazing = 0.18), where the dilution experiment rendered nonsignificant relationship between apparent growth and dilution factor ( R 2 = 0.02, Table ). Although the exact magnitude of these rates should be regarded with caution, we consider that the low rates obtained represent a valid experimental outcome that can contribute meaningfully to the broader interpretation of growth and grazing variability in this region (Landry, ; Latasa, ). Taken together, photo‐physiological measurements and growth rates estimated at stations on the plateau suggested a physiological improvement of phytoplankton relative to waters off the plateau.…”
Section: Discussionmentioning
confidence: 92%
“…[ 13 15 , 18 , 22 ]) or suggested to overestimate the impact of grazing. Indeed, a recent meta-analysis found that many studies erroneously applied tests that assessed the significance of mortality rates based on whether they were greater than or less than zero, rather than strictly greater than zero [ 23 , 24 ]. Other studies have also suggested that grazing rates may be overestimated due to changes within the grazer communities [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…However dilution experiments done in large numbers can be used to describe the process interactions and relationships in natural systems (Landry 2014). This study shows strikingly different responses 5 in predator-prey coupling between eutrophic and oligotrophic systems.…”
mentioning
confidence: 99%